A Phase 1 Study to Evaluate Absolute Bioavailability and Absorption, Distribution, Metabolism, and Excretion of Savolitinib in Healthy Male Volunteers. Issue 4 (19th February 2023) - Miah, Kowser; Vishwanathan, Karthick; Scarfe, Graeme; Li, Yan; Hara, Indira; Cantarini, Mireille; Argue, John; Menakuru, Somasekhar R.
Abstract: Savolitinib is an oral MET (hepatocyte growth factor receptor) tyrosine kinase inhibitor, with demonstrated preliminary efficacy in several cancer types. Previous pharmacokinetics assessments showed that savolitinib is rapidly absorbed but there are limited data on the absolute bioavailability and absorption, distribution, metabolism, and excretion (ADME) of savolitinib. This open‐label, two‐part, phase 1 clinical study (NCT04675021) used a radiolabeled micro‐tracer approach to evaluate absolute bioavailability and a traditional approach to determine the ADME of savolitinib in healthy male adult volunteers (N = 8). Pharmacokinetics, safety, and metabolic profiling and structural identification from plasma, urine, and fecal samples were also assessed. Volunteers received a single oral savolitinib 600 mg dose followed by intravenous 100 μg of [ 14 C]savolitinib in Part 1 and a single oral 300 mg [ 14 C]savolitinib dose (≤4.1 MBq [megabecquerel] [ 14 C]) in Part 2. Following Part 1, absolute oral bioavailability was 69%, the median time of maximum observed concentration was 3.5 hours, and the mean terminal half‐life was 6.1 hours. Following Part 2, 94% of the radioactivity administered was recovered, with 56% and 38% in urine and feces, respectively. Exposure to savolitinib and metabolites M8, M44, M2, and M3 accounted for 22%, 36%, 13%, 7%, and 2%, respectively, of plasma total radioactivity. Approximately 3% of the dose was excreted as unchanged savolitinib in urine. Most savolitinib elimination occurred via metabolism by several different pathways. No new safety signals were observed. Our data show that the oral bioavailability of savolitinib is high and the majority of savolitinib elimination occurs via metabolism and is excreted in the urine.